MAKNA BUDAYA PADA ELEMEN ARSITEKTUR RUMAH GADANG BODI CANIAGO MINANGKABAU DI PROPINSI SUMATRA BARAT - Aulia Abrar (ATRIUM: Jurnal Arsitektur, 2017)
Title: The Meaning of CaniagoStyle of Minangkabau Architecture in West Sumatra Province Minangkabau Traditional Architecture has its own characteristics, both in architectural and philosophical. The shape of the building has a close relationship with the socio-cultural setting of the community. The characteristics of a building can be reviewed through rationalistic qualitative methods based on topology, morphology and typology theories. Traditional architectural elements can be characteristic of an area. So, each of the works created really have a strong and unique foundation, both in terms of structure, facade shape, spatial layout and also the use of its ornaments. The specific form is able to display forms that are in harmony with their environment so that they are able to remind people or the community of that environment. This form makes the Minangkabau architecture easy to remember and known everywhere because whatever is created has a strong foundation and is truly specific.